1989
DOI: 10.1093/jn/119.8.1173
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fructose as Compared to Glucose and Starch Increases the Calcium Content of Kidney of Magnesium-Deficient Rats

Abstract: The effects of feeding diets containing fructose, glucose or starch with or without added magnesium (Mg) on tissue levels of calcium (Ca) in weanling rats were investigated. Rats were fed their respective diet for 4 wk and then fasted overnight. After decapitation, blood was immediately collected, and liver, kidney and heart were removed to determine their Mg and Ca content. Relative kidney and liver weights were greatest in the rats fed the fructose diet. Hypomagnesemia was observed in all animals fed a Mg-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Rats fed a magnesium-deficient, fructoserich diet for 4 weeks had eightfold greater levels of nephrocalcinosis than rats with magnesium-deficient diets with energy derived from glucose or starch. 8 The nephrocalcinosis in the magnesium-deficient fructose diet was accompanied by hypercalciuria and consisted of calcium phosphate, rather than calcium oxalate, deposition. 7 The latter is an intriguing finding given that the initial phase of calcium oxalate stones may be interstitial deposits of calcium phosphate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats fed a magnesium-deficient, fructoserich diet for 4 weeks had eightfold greater levels of nephrocalcinosis than rats with magnesium-deficient diets with energy derived from glucose or starch. 8 The nephrocalcinosis in the magnesium-deficient fructose diet was accompanied by hypercalciuria and consisted of calcium phosphate, rather than calcium oxalate, deposition. 7 The latter is an intriguing finding given that the initial phase of calcium oxalate stones may be interstitial deposits of calcium phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Rats fed high-fructose diets have higher urinary calcium excretion and an eightfold increase in nephrocalcinosis compared to rats fed high-starch diets. 7,8 A study of calcium and phosphorus balance in healthy men consuming controlled diets demonstrated higher urinary losses of calcium as a percentage of calcium intake on a high-fructose versus high-starch diet. 9 In another study on human, intravenous infusion of fructose increased urinary oxalate excretion by 60% compared to glucose infusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in ash content in kidney (ta ble 4) caused by dietary Mg deficiency has been convincingly shown to result from the formation of calcium phosphate and calcium oxalate deposits [4,15,16]. This appears to be dependent on the Mg/Ca ratio in the renal tubule, low ratios being associated with an increased risk of kidney stone formation [17].…”
mentioning
confidence: 99%
“…Experimental studies on rats have shown that high fructose consumption increases urinary calcium excretion and induces nephrocalcinosis [22,23]. Additionally, healthy men given high-fructose diets or an intravenous infusion of fructose developed hypercalciuria, hyperoxaluria, and hyperuricosuria [24,25].…”
Section: Dietary Fructosementioning
confidence: 99%